Tuning on passive interfacial cooling of covalent organic framework hydrogel for enhancing freshwater and electricity generation - Jianfei Wu; Ziwei Cui; Yuxuan Su; Dongfang Wu; Jundie Hu; Jiafu Qu; Jianzhang Li; Fangyuan Kang; Dan Tian; Qichun Zhang; Yahui Cai (SusMat)
Abstract Developing an efficient freshwater and electricity co‐generation device (FECGD) can solve the shortage of freshwater and electricity. However, the poor salt resistance and refrigeration properties of the materials for FECGD put big challenges in the efficient and stable operation of these devices. To address these issues, we propose the covalent organic framework (COF) confined co‐polymerization strategy to prepare COF‐modified acrylamide cationic hydrogels (ACH‐COF), where hydrogen bonding interlocking between negatively charged polymer chains and COF pores can form a salt resistant hydrogel for stabilizing tunable passive interfacial cooling (TPIC). The FECPDs based on the TPIC and salt resistance of ACH‐COF display a maximum output power density of 2.28 W m−2, which is 4.3 times higher than that of a commercial thermoelectric generator under one solar radiation. The production rate of freshwater can reach 2.74 kg m−2 h−1. Our results suggest that the high efficiency and scalability of the FECGD can hold the promise of alleviating freshwater and power shortages.